Study of Environmental Economic Performance According to Energy Use and CO2 Emissions, Air Quality, and Government Policies to Achieve SDGs in Baubau City - Boni, Yohanes; Ariani, Wa Ode Rachmasari; Hasddin, Hasddin (International Journal of Energy Economics and Policy, 2023)
Economic development is required to prioritize aspects of sustainability, namely by not ignoring environmental elements to ensure the benefits of future generations. This study focuses more on presenting development achievement information (in GDP) on ecological performance through energy use, CO2 emissions, air quality, and environmental management by taking the case of medium-scale cities as a differentiator from previous studies. Ecological performance using the standard issued by AGCI. It was found that economic performance was under pressure as indicated by slowing economic growth. Seven sectors make up the GDP structure which is in the process of using energy and producing CO2 emissions. Environmental quality is maintained, and the government’s seriousness in creating environmentally sound economic development is demonstrated by the regulations that govern this matter.